2018
DOI: 10.1002/pen.25025
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of performance of polyamide reverse osmosis membranes using dielectric barrier discharge plasma treatment as a novel surface modification method

Abstract: In this research, surface modification of aromatic polyamide thin film composite (TFC) reverse osmosis (RO) membranes was carried out using dielectric barrier discharge (DBD) plasma treatment to improve the performance and fouling resistance of prepared RO membranes. First, polyamide TFC RO membranes were synthesized via interfacial polymerization of m‐phenylenediamine and trimesoyl chloride monomers over microporous polysulfone support membrane. Next, the DBD plasma treatment with 15 s, 30 s, 60 s, and 90 s d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 46 publications
(59 reference statements)
0
14
0
Order By: Relevance
“…Commonly, the polyamide layer of TFC RO membrane is formed by interfacial polymerization process between an aromatic polyamine such as m ‐phenylenediamine (MPD) in the aqueous phase and aromatic polyacyl halides such as trimesoyl chloride (TMC) in the organic phase on the surface of PSf support . These membranes exhibit superior water flux and salt rejection and excellent chemical, thermal, and mechanical stability in addition to resistance to pressure compaction . However, the major obstacles for application of polyamide TFC RO membranes are fouling, which refers to the deposition of contaminants and unwanted materials on the membrane surface.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly, the polyamide layer of TFC RO membrane is formed by interfacial polymerization process between an aromatic polyamine such as m ‐phenylenediamine (MPD) in the aqueous phase and aromatic polyacyl halides such as trimesoyl chloride (TMC) in the organic phase on the surface of PSf support . These membranes exhibit superior water flux and salt rejection and excellent chemical, thermal, and mechanical stability in addition to resistance to pressure compaction . However, the major obstacles for application of polyamide TFC RO membranes are fouling, which refers to the deposition of contaminants and unwanted materials on the membrane surface.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Fig. c and d, there is no significant improvement of the surface energy of carbon dioxide plasma modified membrane compared to the unmodified one after 100 days of aging . It can be observed from Fig.…”
Section: Resultsmentioning
confidence: 71%
“…Plasma treatment increased the surface energy of PAN by increasing their polar components. Bombardment by plasma species creates free radicals on the polymer surface mainly by chain scission and hydrogen abstraction which subsequently combines with oxygen from air thereby increasing the polarity . Besides the polar groups created at the surface during reactive plasma treatment, it altered surface morphology also .…”
Section: Introductionmentioning
confidence: 99%
“…A more successful commercially available RO membrane is thin film composite (TFC) polyamide membrane for water purification and desalination. [2][3][4] Actually, much work has been developed using TFC polyamide membranes due to their high mechanical, thermal, and hydrolytic stabilities. [5,6] However, these previous works concluded that aromatic polyamide membranes still have inherent weaknesses such as limited oxidant tolerance (due to the presence of electron-rich aromatic rings and secondary amides), minimal fouling resistance, and low chemical and thermal stabilities.…”
Section: Introductionmentioning
confidence: 99%